Dermatologic adverse events associated with epidermal growth factor receptor inhibitors: current concepts of interdisciplinary problem - A. S. Polonskaia; E. A. Shatokhina; L. S. Kruglova (Опухоли головы и шеи)
Epidermal growth factor receptor inhibitors (EGFR) have a high rate of class-specific dermatologic adverse events. Supportive treatment of dermatologic adverse events decreases their severity, minimizes the need for dose de-escalation / discontinuation of targeted therapy, improves commitment to anticancer treatment and patient’s quality of life. Close interdisciplinary cooperation between oncologists and dermatologists is a key to the successful management of patients treated with EGFR. This article highlights current approaches to classification, concepts of pathogenesis and clinical course of EGFR-associated dermatologic adverse events, current and promising prophylactic and therapeutic strategies to manage these adverse events.